Neuropsychological and educational problems at school age associated with neonatal encephalopathy. Issue 5 (19th August 2005) - Marlow, N; Rose, A S; Rands, C E; Draper, E S
Abstract : Background: Adverse cognitive and educational outcomes are often ascribed to perinatal hypoxia without good evidence. Objective: To investigate neurocognitive and behavioural outcomes after neonatal encephalopathy. Methods: Sixty five children with neonatal encephalopathy, identified using the Trent Neonatal Survey database for 1992–1994, were followed up at the age of 7 years. They were examined at school, with a classmate for those in mainstream school, by a paediatrician and a psychologist. Neonatal encephalopathy was graded as moderate or severe using published definitions. Findings: Fifteen children had major disability, all with cerebral palsy; eight were in special school with severe cognitive impairment (IQ<55). Disability was present in 6% of the moderate and 42% of the severe encephalopathy group. Of the 50 children without motor disability, cognitive scores were lowest in the severe group (mean IQ difference from peers −11.3 points (95% confidence interval (CI) −19.0 to −3.6) and with similar scores for the moderate group compared with classmates (mean difference −1.7 points (95% CI −7.3 to +3.9). Neuropsychological testing showed similar findings in all domains. In particular, memory and attention/executive functions were impaired in the severe group. Despite relatively small differences in performance of the moderate group, special educational needs were identified more often in both encephalopathy groups, associated with lower achievement on national curriculum attainment targets. Interpretation: After neonatal encephalopathy, subtle cognitive impairments are found in the absence of neuromotor impairment. Subtle impairments are found more commonly after a more severe clinical course. Studies of brain protection strategies require long term follow up to study effects on cognitive outcome.